Crypsis hypothesis as an explanation for evolution of impermeable coats in seeds is anecdotal. Issue 5 (6th March 2018) - Jaganathan, Ganesh K.
Abstract: Impermeable seed/fruit coat, i.e. physical dormancy (PY) occurring in seeds of many genera of 19 angiosperm plant families has been traditionally viewed as a form of dormancy that regulates germination timing. However, this view was recently challenged by an alternative explanation claiming that the impermeable seed coat evolved as a coping mechanism to escape predators, i.e. crypsis hypothesis. Here, I wish to call for more careful attention on crypsis as an evolutionary factor because (1) information of volatile compounds is not known in PY families except Fabaceace; (2) impermeability is not induced until the moisture content of the seeds drops below species‐specific threshold suggesting that drying determines development of impermeable seed coats; (3) the crypsis hypothesis does not explain the year‐to‐year or between site variations in proportions of impermeable seeds produced by plants; and (4) dry seeds of species from non‐PY families also do not emit volatile compounds, and do not develop impermeable seed coats. For these reasons, it appears crypsis might be an exaptation, i.e., a trait that performs a function for which it was not originally evolved. Based on the available evidence, it is suggested that climate drying might have resulted in evolution of impermeable seed coats.